Assessment of Sleep Quality Among Menopausal Women and its Relationship with Menopausal Symptoms - Twinkle, M J S; Anjali Anand, K; Rajesh, Nisha; George, Jeslin Maria; Shaji, Bipin; Radhakrishnan, Krishnapriya; Shetty, Shraddha; Joel, Juno Jerold (International Journal of Pharmaceutical Investigation, 2026)
Background Menopause is the permanent cessation of menstruation, marked by fluctuating estrogen, irregular periods, sleep disturbances, and various physiological and psychological difficulties. The current study was carried out to assess the sleep quality among menopausal women and its relationship with menopausal symptoms. Materials and Methods A cross-sectional study was conducted for six months in the Department of Obstetrics and Gynaecology of a tertiary care hospital. The Pitts Burgh Sleep Quality Index (PSQI) was used to assess sleep quality, and the Menopausal Rating Scale (MRS) was used to rate the severity of the menopausal symptoms. Statistical analysis was performed using SPSS software version 29.0. Results The study assessed the sleep quality, severity of menopausal symptoms, and their associations among 105 subjects. Sleep quality was predominantly poor among the study subjects, with a moderate positive correlation between menopausal symptoms and sleep quality (R: 0.436, p:< 0.001). A weak positive correlation was observed between age and sleep quality (R=0.204, p=0.019). The findings suggest addressing menopausal symptoms and age-related factors is critical to improve sleep quality. Conclusion Poor sleep quality was prevalent among menopausal women and strongly associated with the intensity of menopausal symptoms. This emphasizes the necessity of therapies to address menopausal symptoms to improve sleep quality and general well-being in this population.
Keywords: Menopause; Menopausal symptoms; Sleep; Sleep quality